Managing Quantity or Quality? Students’ Voices for English Subject in the National Standardized Exam - FRIDIYANTO FRIDIYANTO; MARZUL HIDAYAT; MIFTAHUL KHAIRANI; IMELDA YOSE (Universitas Jambi, Indonesia, 2020)
The issue of quality is always a significant one and it will continue to be one of the predominant points of debate in education. Through a qualitative method, this study aimed to explore the experiences and the meaning that senior high school students faced in the national standardized exam for English subject. The data were collected by demographic background questionnaire and in-depth interviews with fifteen participants. The demographic data were analyzed descriptively, while the interviews were analyzed by within-case and cross-case analyses. The results of the data analysis revealed several themes such as cheating as bad consequences in the national standardized exam, it is like a yearly educational festival and formality, sharpening students memories, spending much money and time for English extra classes, dishonesty: spreading the key answer illegally, teachers more focus on the national exam, it is like a symbol of government power. Recommendations for taking some actions regarding the effect of the national standardized exam are offered.